Shedding light on the existence of Furan fatty acids in latex lipids across a wide diversity of Hevea brasiliensis genotypes - Chaisiri Kitpaosong; Siriluck Liengprayoon; Erwann Durand; Tucksin Lerksamran; Aurélie Daval; Eric Gohet; Lim Khan Tiva; Phean Chetha; Kong Mengchheang; Phen Phearun; Ung Rattana; Kim Chandy; et al. (Journal of Bioresources and Bioproducts)
Furan fatty acids produced by plants and bacteria, and present in some edible resources, have attracted significant scientific attention for their health benefits. They include 10,13-epoxy-11-methyl-octadecan-10,12-dienoic acid, which has been identified in the lipid fraction of latex from two Hevea brasiliensis genotypes commonly known as the source of natural rubber. Those two genotypes, namely RRIM501 and PB235, are from Rubber Research Institute of Malaysia (RRIM) and Prang Besar, Malaysia (PB), respectively. This research aimed to undertake the first ever investigation into the existence of this potential high value-added co-product in the lipid fraction of 48 Hevea brasiliensis genotypes, seeking to study the widest possible clonal variability. The results showed furan fatty acid exists in all lipid fractions of their latices. Its content varied significantly, ranging from 0.01% to 0.71% (w/w in latex), the highest concentrations were found in genotypes from the Institut de Recherche sur le Caoutchouc (IRCA) in Côte d'Ivoire, Prang Besar (PB) in Malaysia, and Rubber Research Institute of Vietnam (RRIV) in Vietnam breeding programs. A positive correlation with total fatty acid content was observed when its content exceeded 0.10%, suggesting an additive rather than a substitutive role with the other fatty acids present. Interestingly, linoleic and palmitoleic acids strongly correlated with the furan fatty acid concentration, indicating a possible biosynthetic pathway linkage. In terms of yield per tapping PB235, RRIV4, RRIV2, IRCA41, IRCA18, PB324, IRCA814, IRCA323, and IRCA109 genotypes showed the highest production potential, with yields range of 1 367–2 446 mg furan fatty acid per tree per tapping. Notably, the biochemical markers of natural rubber productivity (sucrose, inorganic phosphorus, thiols, and total solid content) showed no direct involvement in furan fatty acid biosynthesis during latex regeneration between tappings. Based on knowledge of the parentage of the studied clones, a trait heritability study was conducted and genotype PB5/51 was identified as a very worthwhile genitor for improving furan fatty acid contents in a breeding population.